M. M. Y. Fung et al. (eds.), Xiándai Zhōngguo Shixuan (Modern Chinese Poetry: An Anthology, 1917-1949). Hong Kong, Hong Kong University Press, 1974, 2 vols., xxxix 878, 930. - Maeth Ch., Russell (Estudios de Asia y África, 1978)
-